Decoding the regulatory logic of the Drosophila male stem cell system - Tamirisa, Srividya; Papagiannouli, Fani; Rempel, Eugen; Ermakova, Olga; Trost, Nils; Zhou, Jun; Ruhland, Naima; Boutros, Michael; Lohmann, Jan U.; Lohmann, Ingrid (Cell reports, 2018)
Summary - The niche critically controls stem cell behavior, but its regulatory input at the whole-genome level is poorly understood. We elucidated transcriptional programs of the somatic and germline lineages in the Drosophila testis and genome-wide binding profiles of Zfh-1 and Abd-A expressed in somatic support cells and crucial for fate acquisition of both cell lineages. We identified key roles of nucleoporins and V-ATPase proton pumps and demonstrate their importance in controlling germline development from the support side. To make our dataset publicly available, we generated an interactive analysis tool, which uncovered conserved core genes of adult stem cells across species boundaries. We tested the functional relevance of these genes in the Drosophila testis and intestine and found a high frequency of stem cell defects. In summary, our dataset and interactive platform represent versatile tools for identifying gene networks active in diverse stem cell types.
Gesehen am 07.05.2019